La primera parte de la Visita general de Francisco de Aguiar y Seijas (1682-1698): gobierno y reforma en el arzobispado de México = The first part of the General Visit of Francisco de Aguiar y Seijas (1682-1698) : Government and Reform in the Archbishopric of Mexico - Zaballa Beascoechea, Ana de (Anuario de historia de la Iglesia, 2019)
This article aims to analyze the first two routes followed by Francisco Aguiar y Seijas, archbishop of Mexico, in his General Visit. It focuses on both pastoral and governmental aspects of this institution, which was to become the main means for gaining close knowledge of the territory of the Archbishopric, and thereby governing it effectively. Elements that are taken into account are: the expressions of authority of the archbishop, the defense of his jurisdiction with respect to religious orders, and the archbishop's pastoral concern with matters related to marriage.